Extraction of dietary fiber and phytochemicals from bottle gourd seeds (Lagenaria siceraria), its physicochemical properties and application in food model - Sorokhaibam Romita Devi; Tapasya Kumari; Sankar Chandra Deka (Food Chemistry Advances, 2023)
This research aimed to extract dietary fiber and phytochemicals from matured bottle gourd (Lagenaria siceraria) seeds and use as ingredients in the preparation of cookies. Extraction of dietary fiber was performed using alkaline (AEDF), enzymatic (EEDF), and ultrasound-assisted alkali extraction (UAE). UAE gives a higher yield of 75.81% dietary fiber where the optimized conditions are solute: solvent; 1: 23.90 mg/ml, time; 27.20 min and amplitude; 47.76%. Comparison of physicochemical and functional properties of extracted dietary fiber was done and ultrasound-assisted alkaline extracted dietary fiber (UDF) was found to be the best. Extraction of phytochemicals using ultrasound-assisted alkaline extraction under the condition of 70% amplitude, 45 °C temperature, and duration of 15 min, and identification was done using RP-HPLC analysis and encapsulated using sodium alginate solution (2%) as the wall material. Fiber enriched cookies were developed by incorporating the extracted dietary fiber (3, 6, 9, 12 and 15%) and encapsulated phytochemicals beads (1, 1.5, 2, 2.5 and 3%) in 5 different formulations. The result of this study revealed that matured bottle gourd seeds can serve as a potential, inexpensive dietary fiber source and phytochemicals, which can further be used to develop functional foods.